2010
DOI: 10.1007/s00015-010-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Internal vascularity of the dermal plates of Stegosaurus (Ornithischia, Thyreophora)

Abstract: X-ray computed tomography and petrographic thin sectioning were used to study internal features of the plates of the thyreophoran dinosaur Stegosaurus and the osteoderms of Alligator. Infrared thermographic imaging of basking caimans was used to examine possible differential blood flow to osteoderms and other parts of the skin. Multiple large openings in the Stegosaurus plate base lead to a linear, mesiodistally oriented vestibule, which in turn apically sends off multiply branching ''pipes''. The pipes are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 60 publications
7
77
0
1
Order By: Relevance
“…These theories include the use of dorsal plates for display (Carpenter 1998;Main et al 2005;Hayashi et al 2009), thermoregulation (Farlow et al 1976Buffrénil et al 1986;Farlow et al 2010) and defence (Marsh 1877;Gilmore 1914;Bakker 1986, Mallison 2010. The fact that the plates had a keratinous covering has implications on all these hypotheses, and must therefore be considered when evaluating these suggestions.…”
Section: The Function Of the Dorsal Plates In Stegosauriansmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories include the use of dorsal plates for display (Carpenter 1998;Main et al 2005;Hayashi et al 2009), thermoregulation (Farlow et al 1976Buffrénil et al 1986;Farlow et al 2010) and defence (Marsh 1877;Gilmore 1914;Bakker 1986, Mallison 2010. The fact that the plates had a keratinous covering has implications on all these hypotheses, and must therefore be considered when evaluating these suggestions.…”
Section: The Function Of the Dorsal Plates In Stegosauriansmentioning
confidence: 99%
“…Moreover, keratinous covering in reptiles and birds, like the beaks of birds, are often coloured and interpreted as being used for display (e.g., Tattersall et al 2009). Thermoregulation A thermoregulatory function for the plates has been discussed extensively (e.g., Farlow et al 1976;Buffrénil et al 1986;Main et al 2005;Hayashi et al 2009;Farlow et al 2010), with recent studies accepting a possible exaptation of the plates for this use, although they do not consider it the main function (Main et al 2005;Hayashi et al 2009;Farlow et al 2010). As noted by Farlow et al (1976), a thermoregulatory use would not be optimized through the existence of a keratinous covering.…”
Section: Displaymentioning
confidence: 99%
“…Until recently, most attention for histological patterns in the Thyreophora has been paid to their osteoderms, focusing on the armor of ankylosaurs [16], [20], [58] and on stegosaur plates and spikes [15], [17], [19][21], [58]. The first insights in their long bone histology were provided by the studies of Padian et al [23], describing long bone histology of Scutellosaurus , and by the detailed work on stegosaur long and girdle bone histology by Hayashi et al [19] and Redelstorff and Sander [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that animals such as crocodilians are able to increase and decrease the flow of blood between the core and surface of the body to affect heating and cooling rates [14], and birds are able to increase breathing rates to effect elimination of excess body heat (“panting”) [38]. There is also the ability of lizards to change their skin color from light to dark to improve their ability to absorb the warmth of the sun, with the converse being that a lighter colored skin will absorb less infrared radiation and slow the rate of heating.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal ‘sails’ of late Palaeozoic synapsids such as those of Dimetrodon and Edaphosaurus have been argued to have functioned as radiators [9][12]. Stegosaurian dinosaurs, with their prominent, plate-like osteoderms mounted high on their backs, have also inspired speculations about their ability to lose heat via the extensive vascularization of the plates [13], [14]. However, in the case of the synapsids, it has been shown that the sails were more likely to have been for sexual display based on scaling arguments, and that dorsal sails in small species of Dimetrodon would have been ineffective as radiators [15].…”
Section: Introductionmentioning
confidence: 99%